Determinants of labour market institutions and their reforms from the perspective of economics and political science - Pilc, Michał (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2024)
This presented study is an integrative review of 101 journal articles selected from the Web of Science Social Science Citation Index database in the field of economics and political science, focusing on the determinants of the heterogeneity of labour market institutions, both spatial and temporal. It aims to identify research gaps in the economics literature by comparing it with another social science discipline. The main limitation is found within the mainstream economics, which indicates that labour market institutions are an optimal response of a representative voter to market failures, or the preferred way (by that voter) to redistribute income. The analysis focuses on the spatial heterogeneity of institutions (between countries), with minimal consideration of their temporal evolution. In contrast, political science strongly focuses on selected cases of institutional change, incorporating the preferences and actions of not only voters but also of trade unions, employers’ associations, and political parties. The study concludes that allowing the rational agent to have an impact on the institutional choice through both voting and interest groups would enable mainstream economists to better explain labour market reforms without compromising the discipline’s defining features.